2012
DOI: 10.1371/journal.pone.0050921
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Birth Weight on Plasma, Liver and Skeletal Muscle Neutral Amino Acid Profiles and Intestinal Amino Acid Transporters in Suckling Huanjiang Mini-Piglets

Abstract: Genetic selection strategies towards increased prolificacy have resulted in more and more increased littler size and incidences of impaired fetal development. Low birth weight (LBW) piglets, with long-term alterations in structure, physiology and metabolism, have lower survival rates and poor growth performance. The aim of the study was to compare the plasma, liver and skeletal muscle contents of neutral amino acids (NAA) and the intestinal expression of NAA transporters between LBW and high birth weight (HBW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 29 publications
3
24
0
3
Order By: Relevance
“…The increased serum tAA concentration in IUGR piglets and the decreased mRNA expression of AA transporters indicated an increased body protein catabolism or a reduced protein synthesis rate of piglets when suffering from undernutrition. Similarly, Yang et al has reported that IUGR led to an increase in some of the neutral amino acids contents in plasma, liver, and skeletal muscle compared with their normal littermates, which was accompanied by the inhibition of the mRNA expression of AA transporters [48]. In the present study, mRNA expression of GLUT4 in IUGR-RNI piglets was markedly lower than piglets in other groups.…”
Section: Discussionsupporting
confidence: 69%
“…The increased serum tAA concentration in IUGR piglets and the decreased mRNA expression of AA transporters indicated an increased body protein catabolism or a reduced protein synthesis rate of piglets when suffering from undernutrition. Similarly, Yang et al has reported that IUGR led to an increase in some of the neutral amino acids contents in plasma, liver, and skeletal muscle compared with their normal littermates, which was accompanied by the inhibition of the mRNA expression of AA transporters [48]. In the present study, mRNA expression of GLUT4 in IUGR-RNI piglets was markedly lower than piglets in other groups.…”
Section: Discussionsupporting
confidence: 69%
“…Serum samples were then stored at −80 °C until required for further analyses of D-lactate, diamine oxidase (DAO), and the anti-oxidation index. Piglets were then anesthetized (with C 3 H 2 ClF 5 O) and euthanized by intravenous administration (jugular vein) of 4% sodium pentobarbital solution (40 mg/kg BW) (Yang et al, 2012). The gastrointestinal tract of euthanized piglets was immediately resected and divided into stomach, duodenum, jejunum, ileum, cecum, and colon.…”
Section: Animals Experimental Treatments and Incidence Of Diarrheamentioning
confidence: 99%
“…Multiple exposures of each Western blot were performed to ensure linearity of chemiluminescence signals. Western blots were quantified by measuring the intensity of correctly sized bands using AlphaImager 2200 (Alpha Innotech Corporation, CA, USA) software [14,15].…”
Section: Western Blottingmentioning
confidence: 99%